Green products purchasing among Malaysian consumers (Preliminary study) - Nezakati, Hossein *; Hosseinpour, Masoumeh (2014)
The world is facing with the environmental degradation. Mainly human behaviour is the responsible of this matter. Malaysian government as a part of the world tries to protect the environment. Along with this way, government aims to encourage the public to change their behaviour towards the environment. Therefore, government has been promoted green products for the desired consumers. This study as a primary one aims to discover the awareness of Malaysian people about the green products in the market. In addition, it is aimed to measure the likelihood of intention of consumers to purchase green products. Chi-square analysis and binary logistic regression were applied.